Business Cycle Models, Aggregation, and Real Wage Cyclicality - Bowlus, Audra; Liu, Haoming; Robinson, Chris (Journal of Labor Economics, 2002)
A substantial literature has developed to estimate the “true” cyclicality of real wages, that is, composition bias free. Two major issues are addressed in this article: aggregation of heterogeneous workers and potential bias in the measurement of the labor input. A general analysis of the biases is presented, and alternative approaches in the literature are nested in a single framework. Estimates based on an efficiency units concept that avoids the usual aggregation problems are presented. Composition bias underestimates the usual parameters of interest unless both the price and the quantity of the labor input are adjusted appropriately.